Overcoming the challenges of community-engaged emergency referrals in a rural district of Pakistan - Imran Naeem Abbasi; Siddiqi, Sameen (Journal of the Pakistan Medical Association, 2021)
A functional referral system for addressing maternal and child health issues requires coordinated efforts by health system stakeholders and community. Using Rural Health Program (RHP) Thatta as platform provided by an academic institution, district health system stakeholders and community of Mirpur Sakro taluka of Thatta were engaged to strengthen the emergency referral system for maternal and child health emergencies through active community engagement. Through combined consultation, referral system plan for maternal and child health emergencies was developed. Community volunteers from each village liaised for transportation, referring patients to health facilities and maintaining referral documentation. An ambulance service under contract with health department and private transporters were taken on-board to facilitate patients’ transportation. Community’s experiences of referral system were assessed through qualitative in-depth interviews. Patients’ experiences of referral system improved but faced structural challenges including out of pocket transport expenses, direct self-referrals, Continuous...